Synthesis of ZnO Nanoparticles by Precipitation Method with Their Antibacterial Effect - Muhammad Fajri Romadhan; Nurgaha Edhi Suyatma; Fahim Muchammad Taqi (Universitas Gadjah Mada, 2016)
The aim of this study was to synthesize and characterize Zinc oxide nanoparticles (ZnO-NPs) prepared by precipitation method. Zinc nitrate and sodium hydroxide was used as starting materials with biopolymer pectin as capping agent. ZnO-NPs were synthesized at three levels of temperatures (60, 80 and 100 °C) without or with calcinations (500 °C). Particle size analyzer (PSA) analysis results showed that the samples without calcination (T60, T80 and T100) having an average particle size respectively 105.13, 78.53, and 76.43 nm, whereas at the samples by calcination (T60C, T80C and T100C) each have average particle size of 88.73, 44.30 and 543.77 nm. The results showed that preparation of ZnO-NPs by using heating at 80 °C followed with calcinations at 500 °C (T80C) produced the smallest size. T80C samples further were analyzed using XRD, SEM and the antimicrobial activity compared with the ZnO-NPs commercials. XRD analysis confirmed that ZnO-NPs were successfully obtained and have form of pure nanostructure. SEM analysis showed that ZnO-NPs obtained has a spherical shape. Furthermore, this ZnO-NPs (T80C) has a better antimicrobial activity compared than commercial ZnO-NPs in market.